ANALISIS PENERAPAN TEORI PEMBELAJARAN BRUNER DENGAN KANTONG BILANGAN DALAM MENINGKATKAT HASIL BELAJAR MATEMATIKA PADA SISWA KELAS IV MI NURUL ULUM - rony (Al-mujahidah, 2023)
This research departs from the existence of problems regarding the low mathematics learning outcomes of class IV students at MI Nurul Ulum. This research includes Class Action Research where this research was conducted to improve students' mathematics learning outcomes after the learning stages of Bruner's theory with the help of number bag media. In this study, researchers worked with subject teachers. Learning activities are carried out in two cycles, with each cycle consisting of two meetings. Each cycle has stages, namely planning, implementation of action, observation, and reflection. Then the data collection method used in this study is observation and testing. Based on the results of the analysis, there was an increase in student learning outcomes after the application of Bruner's Learning Theory with number bag media in class IV MI Nurul Ulum I Giligenting Sumenep. In the pre-cycle, there is data obtained at 17.39%. Furthermore, in cycle I there was an increase to 65.21%, and in cycle II there was an increase again to 91.30%. In addition, the results of calculating the N-gain score show a value of 0.37 in the "moderate" category in cycle I, and a value of 0.68 in the "moderate" category in cycle II. With an increase in N-gain data of 0.31 from cycle I to cycle II. Based on the research data and discussion, it can be concluded that the application of Bruner's Learning Theory with number bag media can improve the mathematics learning outcomes of class IV MI Nurul Ulum I Giligenting Sumenep.